Potential interactions between traditional Chinese medicine and osimertinib: a Case Report - Min Zhang; Huiwen Ma; Wanyi Chen; Zhongzhen Yuan (Frontiers in Pharmacology, 2025)
Osimertinib, a third-generation EGFR tyrosine kinase inhibitor, played a crucial role in the treatment of EGFR-mutated non-small cell lung cancer. This case firstly reported a case of drug-drug interaction between traditional Chinese medicine (TCM) and osimertinib. A 57-year-old female was diagnosed with stage IV lung adenocarcinoma, who switched from gefitinib to osimertinib after disease progression. However, the carcinoembryonic antigen (CEA) results suggested biochemical recurrence after 48 months. The first osimertinib trough concentration (Ctrough) was 82.1 ng/mL, significantly lower than the FDA-reported 166 ng/mL, with concurrent elevation of the tumor marker carcinoembryonic antigen (CEA). After excluding other possible factors, the decreased osimertinib concentration might be due to the TCM taken by the patient. After adjusting the TCM prescription, the patient’s osimertinib Ctrough was stable within the range of 145 and 228 ng/mL without significant adverse reactions and carcinoembryonic antigen levels stabilized. This case underscored the importance of monitoring drug concentrations in patients concurrently using TCM and osimertinib to optimize treatment outcomes and minimize potential drug-drug interactions.